Pengaruh Kepercayaan, Fasilitas dan Kecepatan Transaksi Terhadap Kepuasan Nasabah Pada Bank Syarikat Madani Batam - Riswandhi Ismail; Ir. Febri Edward; Muhammad Sidik; Syarifuddin Syarifuddin; M. Arpah; Suyono Suyono (Jurnal Manajemen Bisnis Digital Terkini, 2025)
The purpose of this study is to determine the influence of trust, facilities and transaction speed on customer satisfaction The method used is a questionnaire with a quantitative approach. The types of analysis used are descriptive analysis and verifiable analysis. This research was conducted on Bank Syarikat Madani Batam customers with a sample of 100 respondents. The nonprobability sampling method with the purposive sampling technique is the sampling technique used in this study. The findings in this study show that trust has a significant effect on customer satisfaction. The Facility variable has a t calculation of 19,853 > 1,984 with a significant value of 0.000 < 0.05, then it can be concluded that Facility has a significant effect on customer satisfaction. And the Transaction speed variable has a t calculation of 38,793> 1,984 with a significant value of 0.000 < 0.05, then it can be concluded that Transaction speed has a significant effect on customer satisfaction.